Mobile payment Application Quality and customer Loyalty: A Structural Equation Modeling Approach –BARIDI MOB case study- - Sihem Guidoum; Saadi Elkhansa (المجلة الدولية للأداء الاقتصادي, 2023)
This study examines the relationship between mobile payment app quality and customer loyalty, using the Baridi Mob case. It also investigates the role of customer satisfaction as a mediator. The research model includes app design, privacy, security, reliability, and ease of use, as well as customer satisfaction and loyalty. Data analysis was based on 435 responses. The structural equation modelling technique was used to estimate the hypothesized relationships. The results show that reliability and ease of use have a positive impact on customer satisfaction. Customer satisfaction also has a positive effect on loyalty. Furthermore, customer satisfaction mediates the relationship between service quality and loyalty, with reliability and ease of use being fully mediated and app design being indirectly mediated. Security and privacy do not have a mediated relationship. These findings can be useful for Baridi Mob providers in managing services and improving quality and satisfaction.